Mixed vulnerabilities: the biological risk of high parity is aggravated by emergency referral in Benin, Malawi, Tanzania and Uganda - Manuela Straneo; Lenka Beňová; Thomas van den Akker; Muzdalifat S. Abeid; Elizabeth Ayebare; Jean-Paul Dossou; Greta Handing; Bianca Kandeya; Andrea B. Pembe; Claudia Hanson (International Journal for Equity in Health)
Abstract Identification of interacting vulnerabilities is essential to reduce maternal and perinatal mortality in sub-Saharan Africa (SSA). High parity (≥ 5 previous births) is an underemphasized biological vulnerability linked to poverty and affecting a sizeable proportion of SSA births. Despite increased risk, high parity women rarely use hospitals for childbirth. We assessed whether emergency referral during childbirth was associated with adverse events in high parity women in hospitals in Benin, Malawi, Tanzania and Uganda. We used e-registry data collected in 16 hospitals included in the Action Leveraging Evidence to Reduce perinatal morbidity and morTality (ALERT) trial. Main outcomes were severe maternal outcomes and in-facility peripartum death (fresh stillbirth or very early neonatal death). Main exposure was parity; emergency (in-labour) referral was included as effect modifier with potential confounders. We used multivariable logistic regression including parity/referral interaction and post-regression margins analysis. Among 80,663 births, 4,742 (5.9%) were to high parity women. One third reached hospital following emergency referral. Severe maternal outcomes and peripartum mortality were over 2.5-fold higher in high parity women with emergency referral compared to the lowest risk group. To avert these adverse events, emergency referral must be avoided by ensuring high parity women give birth in hospitals.  Trial registration Pan African Clinical Trial Registry ( www.pactr.org ): PACTR202006793783148. Registered on 17th June 2020.